2019
DOI: 10.1140/epjc/s10052-019-7006-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams of charged compact boson stars

Abstract: Compact boson stars, whose scalar field vanishes identically in the exterior region, arise in a theory involving a massless complex scalar field with a conical potential, when coupled to gravity. Their charged compact generalizations, obtained in the presence of a U(1) gauge field, exhibit further interesting features. On the one hand, charged compact boson shells can arise, whose scalar field vanishes also in the central region, while on the other hand, the domain of existence of charged compact boson stars e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 37 publications
(82 reference statements)
0
22
0
Order By: Relevance
“…of protons and neutrons in heavy ion), strangeness (due to the presence of strange particles in the medium), temperature and density, recently it was found that in HICs, a strong magnetic field is also produced having field strength eB ∼ 2 − 15m 2 π (1m 2 π = 2.818 × 10 18 gauss) approximately [3][4][5]. Since then, physicists are trying to understand how the presence of magnetic field affects the I st and II nd order phase transitions [4,[6][7][8][9]. The time duration for which the magnetic field remains is a very debateable topic.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…of protons and neutrons in heavy ion), strangeness (due to the presence of strange particles in the medium), temperature and density, recently it was found that in HICs, a strong magnetic field is also produced having field strength eB ∼ 2 − 15m 2 π (1m 2 π = 2.818 × 10 18 gauss) approximately [3][4][5]. Since then, physicists are trying to understand how the presence of magnetic field affects the I st and II nd order phase transitions [4,[6][7][8][9]. The time duration for which the magnetic field remains is a very debateable topic.…”
Section: Introductionmentioning
confidence: 99%
“…Many theories suggest that the magnetic field produced in HICs does not die immediately due to the interaction of itself with the medium. The primary magnetic field induces electric current in the matter and due to Lenz's law, a secondary magnetic field comes into picture which slows down the decay rate of the magnetic field [9][10][11][12][13][14][15]17]. These interactions increase the electric conductivity of the medium which further affects the relaxation time of the magnetic interaction and this phenomenon is called the chiral magnetic effect [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations